Effect of open and closed operation modes on the performance of Phase change material based copper heat exchanger - Pakalka, Saulius; Valančius, Kęstutis; Damonskis, Matas (International Conference “Environmental Engineering”, 2020)
Many studies related to latent heat thermal energy storage (LHTES) and performance of phase change materials (PCM) are focused on melting and solidification processes. Investigating and understanding the influence of various parameters on PCMs based thermal energy storage is the key to developing innovative and efficient energy storage systems. The aim of this study is to experimentally compare and assess the performance of phase change material based copper heat exchanger (PCM-HX) in different modes of operation. This PCM-HX is designed to be used in systems where thermal energy can be stored up to 90 °C and an organic PCM RT82 was selected as the energy storage medium. This study focuses on the pressure impact on the PCM melting (charging) and solidification (discharging) processes. Two different modes of operation were analysed: Open and Closed. In the case of an Open mode, the storage tank of PCM-HX was open to the atmosphere (pressure control valve open), in the case of Closed mode the storage tank was closed (pressure control valve closed). PCM charging and discharging processes were conducted and the PCM-HX performances were tested at different pressure inside the storage tank.